ANALISIS PERBEDAAN PENERIMAAN PAJAK DAERAH DAN RETRIBUSI DAERAH PADA KABUPATEN LAMANDAU DAN KABUPATEN SUKAMARA DI KALIMANTAN TENGAH (Students' Journal of Accounting and Banking, 2015)
This study aimed to analyze the differences in local tax revenues and levies to the original income between Lamandau District with Sukamara in Central Kalimantan from 2008-2012. Data analysis method used is quantitative descriptive analysis and trend analysis in percentage to measure the contribution and effectiveness of local taxes and levies and using different test methods Mann-Whitney test to determine differences in local tax revenues and levies between Lamandau District with Sukamara. Results of research conducted showed that there were no differences between the local tax revenue and Sukamara Lamandau District. But there are differences in local tax perjenis especially hotel tax, restaurant tax and entertainment tax between Lamandau District with Sukamara where tax revenue in the District Lamandau higher than Sukamara, while tax receipts restaurants and entertainment tax Sukamara higher than Lamandau District andnot there acceptance of differences between district levies Lamandau with Sukamara, but there are differences in revenue, especially levy local business service between Lamandau District with Sukamara where acceptance Sukamara higher than Lamandau District.Keywords: Local Taxes, Levies Regional, Local Revenue